Risk Factors Associated with Non-Cardiac Congenital Anomalies of Fetus Admitted in Chittagong Medical College Hospital (Cardiovascular Journal, 2020)
Background: Congenital anomalies make an important contribution to infant mortality and they remain a leading cause of death in many countries of the world. Many babies also died in our country due to congenital anomalies.Methods: This retrospective cross-sectional study was conducted at the Departments of Obstetrics and Gynecology of CMCH between October 2016 to March 2017. Objective of the study was to find out the risk factors of non-cardiac congenital anomaly of fetus. The study population of those women who delivered a baby with different non-cardiac congenital anomalies admitted in Departments of Obstetrics and Gynecology of CMCH.Results: The mean maternal age was found 26.6±5.6 years and the mean paternal age was found 35.8±7.9 years. 28 (28.0%) patients had hydrocephalus, 25 (25.0%) had Anencephaly, 7 (7.0%) had Omphalocele, 7 (7.0%) had Hydrops fetalis, 6 (6.0%) had cleft lip, 6 (6.0%) had cleft palate, 4 (4.0%) had cleft lip and cleft palate. 20 (20.0%) patients had consanguinity, history of high-grade fever with rash in first trimester was 12 (12.0%). 16(16.0%) was diabetes mellitus. Majority (63.0%) patients belonged to gestational age 16-28 weeks. The mean gestational age was found 29.5±7.1 weeks with ranged from 16 to 42 weeks. Majority (89.0%) were singleton pregnancy. 60% reveal congenital anomaly in USG.Conclusion: Risk factors of non-cardiac congenital anomalies were consanguinity, maternal obesity, high grade fever with rash in first trimester due to viral infection, diabetes mellitus (uncontrolled), uncontrolled gestational diabetes mellitus, previous birth defect, inadequate intake of folic acid in first trimester, blood group Rh negative, male baby. Hydrocephalus and anencephaly were the most common congenital anomalies.Cardiovasc. j. 2020; 13(1): 40-45